Distribution of Daubenton's bat (Myotis Daubentonii) : why are males and females spatially segregated? - Pasanen Mortensen, Marianne (SLU/Dept. of Ecology, 2009)
Sexual segregation in Daubenton's bat, Myotis daubentonii, whith males and females seperated into different geographic areas, has earlier been documented in areas with differences in altitude and thereby climate. This study provides evidence for segregation also in an area with only small differences in altitude and climate. Sites with both males and females were found, as well as sites with only males. The results indicates that male sites often are located at creeks in agricultural landscapes, while sites with both males and females often are located in or close to a park, nearby a large lake. Different hypotheses which might explain the results are discussed.